Stroke Types in Rural and Urban Northern Portugal: Incidence and 7-Year Survival in a Community-Based Study - Correia, Manuel (S. Karger AG, 2013)
BACKGROUND/AIM: Differences in stroke incidence and mortality between regions could stem from differences in the incidence of particular stroke types and long-term prognosis. The aim of this study was to investigate whether different risk profiles and stroke types underlie the difference in stroke incidence and patient long-term survival in rural and urban populations. METHODS: All suspected first-ever-in-a-lifetime strokes occurring between October 1998 and September 2000 in 37,290 residents of rural municipalities and in 86,023 individuals living in the city of Porto were entered into a population-based registry. Standard definitions of stroke types and overlapping comprehensive sources of information were used for patient identification. Patients were examined by neurologists at 3 months, 1 year and 7 years after the index event. RESULTS: From a total of 688 patients included (226 in rural and 462 in urban areas), 76.2% had an ischaemic stroke (IS; 75.3 vs. 77.9%), 16.1% a primary intracerebral haemorrhage (PICH; 16.3 vs. 14.6%) and 3.3% a subarachnoid haemorrhage (SAH; 2.7 vs. 3.7%); in 4.4% (4.9 vs. 4.1%), the stroke type could not be determined. The annual incidence rate per 1,000 was 2.13 (95% CI, 1.95-2.31), 0.45 (95% CI, 0.37-0.53), 0.09 (95% CI, 0.06-0.14) and 0.12 (95% CI, 0.08-0.17), respectively. The age-specific rural/urban incidence rate ratios for IS in the youngest group (<55 years) was 0.27 (95% CI, 0.11-0.69), increasing to 1.47 (95% CI, 1.07-2.01) for those aged 65-74 years and to 1.87 (95% CI, 1.39-2.52) for those between 75 and 84 years. Rural compared to urban patients with an IS were predominantly men, had a prevalence ratio (PR) of 1.28 (95% CI, 1.05-1.56), were 65 years or older (PR = 1.18; 95% CI, 1.08-1.30) and had in general a lower prevalence of risk factors. There was no evidence of rural/urban differences in 28-day case fatality for the stroke types, although IS tended to be less fatal among urban patients (10.3 vs. 13.1%), whereas PICH (33.3 vs. 24.2%) and SAH (35.3 vs. 16.7%) were less fatal among rural patients. Independently of rural/urban residence, predictors of poor survival after the acute phase (28 days) were age >65 years (HR = 3.57; 95% CI, 2.6-4.9), diabetes (HR = 1.5; 95% CI, 1.2-1.9), ischaemic heart disease (HR = 1.8; 95% CI, 1.3-2.6), atrial fibrillation (HR = 1.5; 95% CI, 1.1-2.0) and smoking habits (HR = 1.6; 95% CI, 1.1-2.3). CONCLUSIONS: The age pattern of IS incidence marks the difference between rural and urban populations; the youngest urban and the oldest rural residents were at a higher risk. Although patients from rural areas were older, the relatively lower prevalence of simultaneously occurring risk and prognostic factors among them as well as the similar management of rural and urban patients may justify why rurality is not associated with long-term survival.